Acoustic Emission and Ultrasonic Characteristics in the Failure Process of Cemented Waste Concrete-Coal Gangue Backfilling (CWCGB) under Uniaxial Loading - Guorui Feng; Tingye Qi; Xianjie Du; Zehua Wang; Yujiang Zhang (Advances in Civil Engineering)
The acoustic emission (AE) characteristics, change law of the ultrasonic velocity, and internal failure mode of cemented waste concrete-coal gangue backfilling (CWCGB) with 600 days of curing time were studied under uniaxial loading conditions. Waste concrete particles of 5 mm acting as fine aggregates substituted for 30% and 50% fine coal gangue in the cemented coal gangue backfilling (CGB). AE was used to test the ring count and changing rule of the accumulated energy, locate the event for positioning, and calculate the number of events. The average ultrasonic wave velocity was measured via an ultrasonic detector. The characteristics of the microfractures were observed via a scanning electron microscope. The results showed that the specimens with 30% and 50% waste concrete replacement rates underwent ultrasonic wave velocity stabilization and a rapid decline stage under uniaxial compression; for the former case, the decline started earlier. The AE ring count attained peaks at the pore compression stage, yield stress point, stress peak value, and residual stress stage with no added waste concrete and 30% and 50% waste concrete substitution rates. The value and consequent frequency of the ringing count peak and cumulative energy slope increased with increasing waste concrete substitution rate. A microcrack was observed at the interfacial transition zone between the cement paste and gangue owing to the alkali-aggregate reaction effect. However, a better bonding performance was exhibited by the waste concrete particles and paste.